2020
DOI: 10.36346/sarjbm.2020.v02i03.006
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Commercial Banks Profitability in Jordan (2005 -2019)

Abstract: The commercial banks remain one of the important keys of financial intermediaries that provides Variety of services in the economy over the states around the world, therefore this paper aims to investigate the profitability of Jordanian commercial banks in Jordan. The effect of internal and external determinants of Commercial Jordanian Banks profitability has been studied in this paper, the paper utilized of annual time series both internal and external data of these determinants for the period 2008 to 2018. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Te healthiness of capital adequacy may improve the income of banks; consequently, enormous capital supports operations to be more fexible in dealing with various investment prospects [26]. Alalaya and Ahmad [27] found that capital adequacy positively and signifcantly related to the fnancial performance of commercial banks measured by ROA at a 5% level of signifcance [28,29]. Moreover, the study conducted by Eric et al [30] reveals that the relationship between capital adequacy and bank profitability was positive [31,32].…”
Section: Capital Adequacymentioning
confidence: 99%
See 1 more Smart Citation
“…Te healthiness of capital adequacy may improve the income of banks; consequently, enormous capital supports operations to be more fexible in dealing with various investment prospects [26]. Alalaya and Ahmad [27] found that capital adequacy positively and signifcantly related to the fnancial performance of commercial banks measured by ROA at a 5% level of signifcance [28,29]. Moreover, the study conducted by Eric et al [30] reveals that the relationship between capital adequacy and bank profitability was positive [31,32].…”
Section: Capital Adequacymentioning
confidence: 99%
“…For this study, liquidity was measured by the ratio of total liquid assets to total deposits and cash to total deposits. According to Alalaya and Ahmad [27], Eric et al [30], Jaouad and Lahse [52], Kryeziu and Hoxha [33], and Mahmud et al [34], the liquidity level infuences the bank proftability positively.…”
Section: Management Efciencymentioning
confidence: 99%
“…Therefore, this study aims to investigate whether CIT influences the Palestinian company's financial performance and market value. Taking into account the political risk and unstable environment in the Palestinian context, this area is exposed to political risk and instability for quite a long time (Alalaya, & Al Khattab, 2015;Elfeituri, 2022).…”
Section: Introductionmentioning
confidence: 99%